Determinants of return to play after the nonoperative management of hamstring injuries in athletes. A systematic review - Fournier-Farley, C.; Lamontagne, M.; Gendron, P.; Gagnon, D. H. (The American Journal of Sports Medicine, 2016)
Background: It is important for clinicians to rely on suitable prognosis factors after hamstring injuries because of the high incidence of these injuries and time away from athletic activities. Purpose: To summarize the current literature on factors that influence return to play after a hamstring injury in athletes. Study Design: Systematic review. Methods: A computer-assisted literature search of CINAHL, MEDLINE, Embase, and EBM Reviews databases (and a manual search of the reference lists of all selected articles) was conducted using keywords related to hamstring injuries and return to play. The literature review criteria included (1) patients with an acute hamstring or posterior thigh injury; (2) a randomized controlled trial, cohort study, case-control study, case series, or prospective or retrospective design; (3) information on rehabilitation, physical therapy, clinical assessment, imaging techniques, and return to play; and (4) studies written in English or French. Results: The search strategy identified 914 potential articles, of which 24 met the inclusion criteria. In terms of the clinical assessment, the following factors were associated with a longer recovery time: stretching-type injuries, recreational-level sports, structural versus functional injuries, greater range of motion deficit with the hip flexed at 90°, time to first consultation >1 week, increased pain on the visual analog scale, and >1 day to be able to walk pain free after the injury. As for magnetic resonance imaging studies, the following factors correlated with a longer recovery time: positive findings; higher grade of injury; muscle involvement >75%; complete transection; retraction; central tendon disruption of the biceps femoris; proximal tendon involvement; shorter distance to the ischial tuberosity; length of the hamstring injury; and depth, volume, and large cross-sectional area. With respect to ultrasound studies, the following factors were associated with a poor prognosis: large cross-sectional area, injury outside the musculotendinous junction, hematoma, structural injury, and injury involving the biceps femoris. Lastly, rehabilitation approaches that included hamstring loading during extensive lengthening or 4 daily sessions of static hamstring stretching led to shorter rehabilitation times. Conclusion: Numerous determinants have an effect on return to play after a hamstring injury in athletes. It is important for sports professionals to be aware of those determinants to guide athletes through the rehabilitation process and refine return-to-play strategies